Morphological characterization and photocatalytic efficiency measurements of pure silica transparent open-cell sponges coated with TiO2 - Löffler, Frank (2020)
Transparent glass sponges are a new class of materials that can potentially be used for effective light distribution in photocatalytic applications. In this work, transparent glass sponges are prepared by the polymer replica technique and coated with TiO2 to obtain a highly efficient photocatalytic material. Necessary conditions for obtaining transparent open-celled glass sponges are presented. The structure is characterized by employing light microscopy and scanning electron microscopy. In addition, µ-computer tomography (µ-CT) volume image analysis was performed that allows the calculation of geometrical parameters like pore size and specific surface area (SSA) of the structure, required for application of the new material. For photocatalytic application, the sponges have been coated with titanium dioxide (TiO2) by immersion in a suspension of TiO2 nanoparticles. The activity of the resulting coatings has been tested with the model reaction of transformation of Cr(VI) to Cr(III) in aqueous solutions in the presence of EDTA at pH 2. The reaction kinetics could be adjusted to a pseudo-first order reaction and the obtained rate constants have been employed to evaluate the photocatalytic activity. The activity of the sponges has been compared with that of samples of glass plates coated with TiO2; it has been found that the sponges exhibited a higher catalytic activity than the glass plates. The photocatalytic activity increased with the porosity of the sponges, and the optimum sample was determined based on its photocatalytic performance and its mechanical stability. The results are promissory for application in photoreactors for transformation of pollutants in water and air decontamination.